The Combined Effect of Ergonomic Factors on Work and Cognitive Performance in The Automotive Industry - Murugesan, Mani; Ramesh Babu Thangavelu; Vimalanathan Komalanathan (International Journal of Industrial Engineering: Theory, Applications and Practice, 2025)
The study aimed to explore the impact of combined ergonomic factors on the work and cognitive performance of final inspection workers (n=18) in the automotive industry. Three levels of ergonomic factors were studied: posture, mental workload, and work shift. The Poison Test and Digit Symbol Substitution Test were used to assess the work and cognitive performance of final inspectors. Results found that posture and mental workload significantly impact work performance (15.22%) and cognitive performance (10.21%), while mental workload and work shift significant-ly impact both (2.98%) and (1.81%). Work shift and posture also substantially impact both (6.61%) and (4.96%). The combined effects of posture, workload, and Work shift significantly impacted both work performance (5.24%) and cognitive performance (7.88%). The study reveals that posture, mental workload, and work shift significantly impact the work and cognitive performance of final inspection workers in the automotive industry.